Stratification of lung adenocarcinoma patients for d-limonene intervention based on the expression signature genes. Issue 16 (22nd June 2021) - Zhu, Tengteng; Li, Qiang; Xu, Liming; Zhang, Qi; Lv, Wenwen; Yu, Herbert; Feng, Tienan; Qian, Biyun
Abstract : Globally, lung cancer ranks as the most lethal malignant neoplasm. Abstract : Globally, lung cancer ranks as the most lethal malignant neoplasm. d -Limonene, a plant extract enriched with essential oils, has been reported to exert anti-cancer effects both in vitro and in vivo ; however, its clinical effect on humans remains elusive. Therefore, the present study aimed to investigate the gene expression signature that would potentially stratify lung adenocarcinoma (LUAD) patients who may benefit from d -limonene intervention, thus facilitating the development of newer treatment strategies for LUAD. In total, 1877 significant differentially expressed genes (DEGs) were identified. These genes were mainly associated with the metabolism of terpenoids and polyketides, lipid metabolism, endocrine system, carbohydrate metabolism, and cell growth and death pathways. Three genes, including antioncogenes FZD3 and MTURN, and oncogene PRC1, which were regulated by d -limonene were identified based on survival analysis of TCGA–LUAD data and were validated by both in vitro and in vivo experiments. High-risk patients screened by the model exhibited a significantly poor prognosis. In conclusion, three gene expression signatures ( FZD3, MTURN, and PRC1 ) were validated by both in vitro and in vivo experiments and identified to help stratify candidate lung adenocarcinoma patients who may benefit from d -limonene intervention. Although further studies are warranted, this study highlighted a potential strategy to improve the treatment outcomes of LUAD patients.